1993
DOI: 10.1161/01.cir.88.4.1746
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair in rheumatic disease. The flexible solution.

Abstract: BACKGROUND Mitral valve repair in rheumatic disease is technically more difficult, and there is little information on the long-term stability of this technique. METHODS AND RESULTS From January 1975 to December 1990, 327 patients underwent mitral valve repair with the Duran flexible ring annuloplasty for rheumatic valve disease. Mean age was 45.4 +/- 12.6 years (range, 23 to 73 years). The techniques used for valve repair include a Duran flexible ring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Long-term results showed ventricular function restored to normal levels, significantly improved survival ratios in particular following solely mitral procedures 34 , which in the present work were performed in 71.8% of the patients. Associated with this was the introduction of various valve repair techniques 13,21,40,41 as well as recognition of the problems caused by valve replacement procedures like prosthesis degeneration, infection, transvalvular gradients, paravalvular leaking, hemolysis, and thromboembolic events 8,37 .…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Long-term results showed ventricular function restored to normal levels, significantly improved survival ratios in particular following solely mitral procedures 34 , which in the present work were performed in 71.8% of the patients. Associated with this was the introduction of various valve repair techniques 13,21,40,41 as well as recognition of the problems caused by valve replacement procedures like prosthesis degeneration, infection, transvalvular gradients, paravalvular leaking, hemolysis, and thromboembolic events 8,37 .…”
Section: Discussionsupporting
confidence: 54%
“…This permitted the achievement of a better result, 65% of the patients passing to functional class I with recovery of left ventricular geometry and mechanical function of the mitral valve, as is also reported in the literature 26,28,34,35 . A follow-up period of 16 months showed a survival ratio of 93.8%; other studies, with lower 29 or equal 36 follow-up periods, reported 98% indexes.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations